Lack of Awareness About Obstetrics Physical Therapy in Pakistan - Rabia Khan; Muhammad Usman; Ghousia Shahid (Journal of Bahria University Medical and Dental College)
This letter aims to explain the role of obstetrical physical therapy in pregnancy to highlight the awareness related to physical therapy in Pakistan